Level of Patient Satisfaction with Pharmaceutical Services in Pasar Ujungbatu Padang Lawas Health Center in 2023 - Harahap, Hasni Yaturramadhan; Debi Meilani (Pustaka Media Publishing, 2023)
Quality pharmaceutical services are health services that can satisfy every service user in accordance with the level of patient satisfaction and the administration is in accordance with the established code of ethics and service standards. The purpose of this study was to determine the level of patient satisfaction with pharmaceutical services at the Pasar Ujungbatu Health Center, Padang Lawas Regency, Padang Lawas Regency in 2023. The research method included a descriptive method, namely using a quantitative approach to determine the level of patient satisfaction with pharmaceutical services at the Ujungbatu Market Health Center, Padang Lawas Regency. The results showed the level of patient satisfaction with pharmaceutical services at Pasar Ujungbatu Padang Lawas Health Center in 2023 with a total of 240 respondents, namely 2 people were very dissatisfied (0.83%), 4 people were dissatisfied (1.66%), 34 people were quite satisfied (14.16), 162 people were satisfied (67.5%), and 38 people were very satisfied (15.85%).